An Effective Ant Colony Optimization Methodology For Virtual Machine Placement In Cloud Data Centre - et. al., A. Arivuselvi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A Cloud environment is a type of service-oriented computer application, and its services comprise SaaS, IaaS, PaaS, and XaaS. The cloud user chooses essential services from dust, and those service models fulfill customers' incoming tasks with service contracts. Each task is executed in Physical Machine (PM) deployed in the cloud through Virtual Machine (VM), so VM plays a vital role in the cloud environment. A cloud would be a pay as you go platform, and hence many VMs within the physical servers can be created and destroyed. The effective allocation of virtual machines to physical machines permits the economic sharing of physical devices to obtainable data centers. These allocation strategies facilitate measuring and enhancing the performance of the cloud. The focus of this work is to put forward a VM migration technique in the cloud environment, which improves the CPU and memory utilization with reduced traffic congestion in the cloud data centers using bioinspired algorithms. The proposed approach improves the memory management, reduces the traffic, and maximizes CPU utilization the current state of the VMs and PMs is not interrupted.